Anne of Green Gables - Tanaka, Shelley; Montgomery, L. M., (Lucy Maud), 1874-1942. (New York : Bantam Doubleday Dell Books for Young Readers, 1998)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely, middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her.
"A Yearling book.".
L.A. Recommended Foreign Language.
Library Talk.
3.8
3-6
Keywords: Country life -- Prince Edward Island -- Fiction; Friendship -- Fiction; Orphans -- Fiction; Country life -- Prince Edward Island -- Fiction; Friendship -- Fiction; Orphans -- Fiction; Prince Edward Island -- Fiction; Prince Edward Island -- Fiction